Exact-Dimensional Property of Density of States Measure of Sturm Hamiltonian. (19th March 2017) - Qu, Yanhui
Abstract: For frequency $α$ of bounded type and coupling $λ>20$, we show that the density of states measure ${\mathcal N}_{α, λ}$ of the related Sturm Hamiltonian is exact upper and lower dimensional, however, in general it is not exact dimensional.